Impact Behavior of Recycled Aggregate Concrete Based on Split Hopkinson Pressure Bar Tests - Yubin Lu; Xing Chen; Xiao Teng; Shu Zhang (Advances in Materials Science and Engineering)
This paper presents the experimental results of recycled aggregate concrete (RAC) specimens prepared with five different amounts of recycled coarse aggregate (RCA) (i.e., 0, 25%, 50%, 75%, and 100%) subjected to impact loading based on split Hopkinson pressure bar tests. Strain-rate effects on dynamic compressive strength and critical strain of RAC were studied. Results show that the impact properties of RAC exhibit strong strain-rate dependency and increase approximately linearly with strain-rate. The transition point from low strain-rate sensitivity to high sensitivity decreases with the increase of matrix strength.